Dynamic response of Ti3SiC2 under shock compression up to 112 GPa. Issue 15 (1st August 2021) - Xu, Liang; Li, Xuhai; Cui, Yihang; Li, Zhiguo; Chen, Qingyun; Meng, Chuanmin; Zhang, Haibing; Hu, Jianbo; Wu, Qiang
Abstract: Ti3 SiC2 is of interest due to its unique dual nature reminiscent of both brittle ceramics and ductile metals at ambient conditions. In this work, plate-impact experiments have been performed to study the dynamic behavior of Ti3 SiC2 under shock compression up to 112 GPa by using laser velocity interferometer and electric pin techniques. Hugoniot elastic limits (HEL), spall strength, and Hugoniot equations of state have been obtained based on measured particle velocity profiles and shock wave velocities. The ratio of spall strength to HEL for Ti3 SiC2 is larger than brittle ceramics but smaller than metals. This result indicates that the dual nature of Ti3 SiC2 remains at least up to 10 GPa. On the other hand, the linearity of the Hugoniot equation of state, D = 6.9 0 1 ( 22 ) + 1.153 ( 53 ) u p, suggests that the initial structure of Ti3 SiC2 should be stable up to 112 GPa, in contrast to the result reported by Jordan et al. [J. Appl. Phys., 93 (2003) 9639].